2014
DOI: 10.1371/journal.pone.0086407
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Endothelial Growth Factors Enhance the Permeability of the Mouse Blood-brain Barrier

Abstract: The blood-brain barrier (BBB) impedes entry of many drugs into the brain, limiting clinical efficacy. A safe and efficient method for reversibly increasing BBB permeability would greatly facilitate central nervous system (CNS) drug delivery and expand the range of possible therapeutics to include water soluble compounds, proteins, nucleotides, and other large molecules. We examined the effect of vascular endothelial growth factor (VEGF) on BBB permeability in Kunming (KM) mice. Human VEGF165 was administered t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
68
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(73 citation statements)
references
References 43 publications
3
68
1
1
Order By: Relevance
“…Additionally, its neurovascular protective effects were associated with a reduction of VEGF-MMP-9 expression (Won, et al, 2014). Consistent with this observation, we and others have shown that exogenous application of VEGF can increase BBB permeability (Jiang, et al, 2014, J. Wang, et al, 2015).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Additionally, its neurovascular protective effects were associated with a reduction of VEGF-MMP-9 expression (Won, et al, 2014). Consistent with this observation, we and others have shown that exogenous application of VEGF can increase BBB permeability (Jiang, et al, 2014, J. Wang, et al, 2015).…”
Section: Discussionsupporting
confidence: 90%
“…Studies have shown that an increase in VEGF expression and downregulation of NKA activity are associated with the aggravation of brain injury (Jiang, et al, 2014, Yang, et al, 2012). The activity of NKA in brain can be downregulated by phosphorylation of the α subunit at Ser23 by PKC or Ser943 by PKA (Yang, et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…This gives plenty of opportunity to RGL stem cells in the developing dentate gyrus (50,51) to receive similar cues and participate in the BBB via the wrapping of blood vessels. Furthermore, exogenous VEGF has been shown to increase the permeability of the BBB (96,97). So the endogenous release of VEGF from perivascular RGL stem cell processes could participate in the induction of vasculogenesis and facilitate an increase in blood-to-brain signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies suggested that VEGF enhances BBB permeability. [30][31][32] Increased VEGF expressions were observed after brain damage in experimental animal models [33][34][35] and in patients with brain damage. 8,36,37) Argaw et al 27) focused on astrocytic VEGF-A as a key driver of BBB permeability and confirmed that the inactivation of astrocytic VEGF-A reduced BBB breakdown, lymphocyte infiltration and inflammatory damage in a mouse model of multiple sclerosis (MS).…”
Section: Targets Of Therapeutic Drugs For Bbb Disruptionmentioning
confidence: 99%